2021
DOI: 10.1109/access.2021.3053034
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Loss From Localization Error in MIMO Channel Using Leaky Coaxial Cable

Abstract: Leaky coaxial (LCX) cable has been employed as antennas for wireless traffic over many linear-cell scenarios such as railway station, tunnels and shopping malls. In addition, LCX can be used for user localization and wireless power transfer (WPT). Compared with the equal power allocation method, the power allocation method for LCX system using positional information (PI) can improve its capacity with the same level of computational complexity. In this paper, we will investigate the level of capacity loss on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In [13], it performs a field measurement of the LCX-MIMO channel in the tunnel and verifies the stability of LCXs used as the radio propagation medium. In [14], it was confirmed that the LCX system can reduce the capacity loss by using position information than that of other systems. For channel modeling, according to the radiation characteristics of LCX in the tunnel, a geometrically-based single-bounce multiple-input-multiple-output (GBSB-MIMO) channel model can be better used to model the LCX channel under the tunnel to simulate the channel statistics and coverage performance [15,16].…”
Section: Introductionmentioning
confidence: 91%
“…In [13], it performs a field measurement of the LCX-MIMO channel in the tunnel and verifies the stability of LCXs used as the radio propagation medium. In [14], it was confirmed that the LCX system can reduce the capacity loss by using position information than that of other systems. For channel modeling, according to the radiation characteristics of LCX in the tunnel, a geometrically-based single-bounce multiple-input-multiple-output (GBSB-MIMO) channel model can be better used to model the LCX channel under the tunnel to simulate the channel statistics and coverage performance [15,16].…”
Section: Introductionmentioning
confidence: 91%
“…In order to further study the factors that may affect the performance of an LCX MIMO wireless channel, Dr. Yafei Hou and his team studied the impact of user location information on the performance of an LCX MIMO wireless channel [ 11 , 12 , 13 , 14 ]. A composite leaky cable based on user location information and a low complexity power allocation scheme is proposed for a 4 × 4 MIMO system in [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A composite leaky cable based on user location information and a low complexity power allocation scheme is proposed for a 4 × 4 MIMO system in [ 11 ]. The results showed that the error of user location information could lead to loss of channel capacity for an LCX MIMO system [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%